Hamster Kombat: Excursus into a Blockchain Game - Mihai Burlacu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
“Hamster Kombat” is one of the last evolutions in a long line of token-based projects that promised one of the most attractive airdrops in the history of blockchain cryptocurrency. In this article I expound an anthropological excursus about it. I intend to emphasize new perspectives into the ways in which digital activities and artefacts are imagined and represented on this blockchain game. Drawing upon publications from the past two decades, I use Hamster Kombat as an example to draw attention to the relevance of blockchain games for digital anthropologists.